2012
DOI: 10.1103/physrevb.86.094417
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state phase diagram of a spin-12frustrated ferromagnetic XXZ chain: Haldane dimer phase and gapped/gapless chiral phases

Abstract: The ground-state phase diagram of a spin-1 2 XXZ chain with competing ferromagnetic nearestneighbor (J1 < 0) and antiferromagnetic second-neighbor (J2 > 0) exchange couplings is studied by means of the infinite time evolving block decimation algorithm and effective field theories. For the SU(2)-symmetric (Heisenberg) case, we show that the nonmagnetic phase in the range −4 < J1/J2 < 0 has a small but finite ferromagnetic dimer order. We argue that this spontaneous dimer order is associated with effective spin-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 84 publications
11
136
0
Order By: Relevance
“…It has been shown that in the case of δ = 0 (γ xy δ = γ z± δ = 0) and g = 0 (γ ssc = γ ′ ssc = 0), the gapless chiral phase can appear as the coupling constant γ tw grows on the renormalization group flow for a certain range of J 1 /J 2 < 0 and 0 < ∆ < 1 [Refs. 10,23]. The bond alternation of J 1 immediately locks the field √ 4πφ + to either 0 or π depending on the sign of J 1 δ and uniformly shifts the locking position of √ 4πθ − from ±π/2, since it provides relevant interactions with the coupling constants γ xy δ and γ z+ δ .…”
Section: Abelian Bosonization Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that in the case of δ = 0 (γ xy δ = γ z± δ = 0) and g = 0 (γ ssc = γ ′ ssc = 0), the gapless chiral phase can appear as the coupling constant γ tw grows on the renormalization group flow for a certain range of J 1 /J 2 < 0 and 0 < ∆ < 1 [Refs. 10,23]. The bond alternation of J 1 immediately locks the field √ 4πφ + to either 0 or π depending on the sign of J 1 δ and uniformly shifts the locking position of √ 4πθ − from ±π/2, since it provides relevant interactions with the coupling constants γ xy δ and γ z+ δ .…”
Section: Abelian Bosonization Analysismentioning
confidence: 99%
“…(22), (23), and (24) hold at least for gh = 0. Then, we expand the self-consistent equations of the mean-field decoupling approximation, Eqs.…”
Section: B Effects Of the Staggered Scalar Chiral Interaction On Thementioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with a maximun gap around α = 0.6 at weak dimerization (β = 0.9). On the other hand, an adiabatic connection of the AKLT-type VBS state from β = 0 to 1 was predicted by the field-theoretical analysis for |J 1 | J 2 [29]. A contour plot of the magnitude of ∆ is given in Figure 2.…”
mentioning
confidence: 99%